Experimental and Numerical Applications to Increase Thermal Performance of a Photovoltaic Solar Panel - Catalkaya, Murat (Fırat Üniversitesi, 2025)
Recently, the impact of global warming has intensified interest in renewable energy sources as alternatives to fossil fuels. Among these resources, solar energy stands out due to its potential. Photovoltaic (PV) panels play a crucial role in converting solar energy into electrical energy. However, one of the biggest challenges in generating electricity with PV panels is that approximately 80% of the energy from the panel surface is transformed into heat. This temperature increase on the PV panel surface negatively affects its efficiency, making it essential to find effective cooling solutions. In this study, we developed numerical analysis methods to investigate the effects of monocrystalline PV panels on passive cooling under the climatic conditions of Kahramanmaraş. First, we performed experimental investigations to assess the performance of the photovoltaic solar panels. The experiments revealed an average panel surface temperature of 43.54°C, with solar radiation and panel power measuring 785 W/m² and 36.32 W, respectively. We then employed ANSYS Fluent software for numerical analysis. The experimental data were utilized to determine the most suitable solution network structure for computational fluid dynamics (CFD) analyses, resulting in a CFD model of the PV panel with a surface temperature error of just 2.44%. The CFD model was used to examine how different fin sizes and distances between fins affected cooling on the PV panel surface. The CFD analysis indicated that increasing the distance between the fins by approximately 40% (5 mm) led to a reduction of about 4°C in fin tip temperature compared to the original fin geometry

Son zamanlarda küresel ısınmanın etkileri, fosil yakıtlara alternatif olarak yenilenebilir enerji kaynaklarına olan ilgiyi artırmaktadır. Bu kaynaklar içerisinde güneş enerjisi, potansiyeli sebebiyle ayrı bir öneme sahiptir. Fotovoltaik (PV) paneller güneş enerjisini elektrik enerjisine dönüştürür. Fotovoltaik panellerle elektrik üretmenin en büyük sorunlarından biri, panel yüzeyine gelen enerjinin yaklaşık %80'inin ısıya dönüşmesidir. Bu dönüşüm sırasında PV panel yüzeyinde meydana gelen sıcaklık artışı panel verimliliğini olumsuz etkilemektedir. Dolayısıyla, panellerin verimli çalışabilmesi için soğutulması, çözülmesi gereken bir problem haline gelmektedir. Bu çalışmada; Kahramanmaraş iklim koşullarında monokristal PV panelin pasif soğutma üzerindeki etkilerini incelemek için sayısal analiz yöntemleri geliştirilmiştir. Öncelikle incelenecek olan fotovoltaik güneş panelinin performansı deneysel olarak araştırılmıştır. Yapılan deneylerde ortalama panel yüzey sıcaklığı 43.54°C , güneş ışınımı ve panel güçü sırasıyla 785 W/m2, 36.32 W bulunmuştur. Daha sonra sayısal analiz için ANSYS-Fluent yazılımı kullanılmıştır. Yapılan hesaplamalı akışkanlar dinamiği (HAD) analizleri için en uygun çözüm ağı yapısını belirlemek üzere deneysel veriler kullanılmış ve Ansys programında yüzey sıcaklığı için yapılan PV panelin HAD modeli 2.44% hatayla model oluşturulmuştur. HAD modeline deneysel çalışma senaryolarında çeşitli kanat boyutları ve kanatlar arasında ki mesafenin PV panel yüzeyinde ki soğutma ya olan etkili incelenmiştir. HAD analizleri sonucunda kanat geometrisine nazaran, kanatlar arasında ki mesafede ki yaklaşık %40 lik (5mm) artışta kanat uç sıcaklığında yaklaşık 4°C bir azalma elde edilmiştir.
Fotovoltaik Bir Güneş Panelinin Termal Performansını Arttırmak için Deneysel ve Sayısal Uygulamalar
Keywords: Energy Generation; Conversion and Storage (Excl. Chemical and Electrical); Enerji Üretimi; Dönüşüm ve Depolama (Kimyasal ve Elektiksel hariç); Optimization Techniques in Mechanical Engineering; Makine Mühendisliğinde Optimizasyon Teknikleri; Numerical Methods in Mechanical Engineering; Makine Mühendisliğinde Sayısal Yöntemler